Investigations on air-fuel mixing and flame characteristics of biodiesel fuels for diesel engine application. (15th November 2017) - Hwang, Joonsik; Bae, Choongsik; Patel, Chetankumar; Agarwal, Rashmi A.; Gupta, Tarun; Kumar Agarwal, Avinash
Highlights: The biodiesel fuels showed poor atomization characteristics than diesel. The SMD values of biodiesel fuels were 13% larger than diesel. Biodiesel fuels had leaner air-fuel mixture than diesel due to oxygen species. Biodiesel fuels showed faster soot oxidation process than diesel fuel. Abstract: In this study, the spray and combustion phenomena of biodiesels were investigated in a constant volume combustion chamber (CVCC). Mineral diesel was used as a baseline fuel and biodiesels derived from waste cooking oil, Karanja oil, and Jatropha oil were utilized to investigate the effect of fuel properties on spray and combustion processes. Experiments were performed at high temperature and pressure conditions in order to simulate the atmospheric environment of a diesel engines. Test fuels were injected at an injection pressure of 80 MPa using a common-rail equipped solenoid injector. Macroscopic evaporation characteristics were analyzed by high-speed shadowgraphy technique under evaporating conditions. The representative droplet size distribution and Sauter mean diameter (SMD) were measured using the Phase Doppler Interferometry (PDI) technique, which was applied to study the spray atomization characteristics of the fuels. The air-fuel equivalence ratio in the spray was calculated using mathematical correlations. The quantitative estimations of soot generation in the spray flames were compared using Hue number analysis. From the shadowgraphy images, the biodiesels showed slower air-fuel mixing characteristics than the baseline diesel due to their inferior volatility. While diesel evaporated abruptly after the fuel injection, the biodiesels showed dense liquid regions in the center of the spray plume. Biodiesels also exhibited larger SMD than the baseline mineral diesel in the fuel spray because of their higher density, viscosity, and surface tension. Despite having poor spray atomization characteristics, the calculated equivalence ratio of biodiesels was lower than that of the baseline diesel. This trend was attributed to the oxygen content of biodiesel. The flame luminosity and visible spray flame duration of biodiesels were lower than those of diesel, while the biodiesel spray flames exhibited lower sooting tendency than the baseline diesel.